Compounds from Cyclocarya paliurus leaves inhibit binary division of methicillin-resistant Staphylococcus aureus by disrupting FtsZ dynamic - Chen, Wenlong; Zhang, Shuixian; Huang, Chunxu; Hu, Zhiming; Cao, Ting; Mou, Jun; Gu, Xinxia; Sun, Meiling; Liu, Jie (Frontiers in Microbiology, 2025)
The escalating threat of methicillin-resistant Staphylococcus aureus (MRSA) necessitates novel therapeutic strategies. Our previous work suggested that an extract from Cyclocarya paliurus leaves (ECPL) inhibits MRSA by targeting the cell division protein FtsZ. Here, guided by anti-MRSA activity, we isolated three compounds from ECPL: asiatic acid (AA), maslinic acid (MA), and ursolic acid (UA). They exhibited antibacterial activity against MRSA and induced cell elongation, indicative of division arrest. Time-kill assays showed AA and MA are bactericides, while UA is bacteriostatic. Mechanistically, these compounds disrupt cell division by differentially affecting FtsZ dynamics: AA promotes polymerization, whereas MA and UA inhibit it. SPR analysis showed direct FtsZ binding to AA (Kd = 2.4 μM), MA (Kd = 9.8 μM), and UA (Kd = 0.7 μM). Molecular docking predicted a shared FtsZ binding pocket but revealed that AA adopts a distinct conformation driven by unique interactions, including a hydrogen bond with Arg191—an interaction not observed for MA or UA, which instead form hydrogen bonds with Thr265 and Thr309. Despite these divergent effects on polymerization and distinct binding modes, all compounds ultimately disrupted Z-ring assembly and septum formation. In a murine skin infection model, AA, selected for its bactericidal activity and unique FtsZ modulation mechanism, significantly reduced bacterial burden and accelerated wound healing. Collectively, our findings validate these compounds as direct FtsZ-targeting agents and establish AA as a promising anti-MRSA lead compound with a novel mechanism disrupting the bacterial divisome.